Short-term training effects of vertically and horizontally oriented exercises on neuromuscular performance in professional soccer players - Los Arcos, A.; Yanci, J.; Mendiguchia, J.; Salinero, J. J.; Brughelli, M.; Castagna, C. (International Journal of Sports Physiology and Performance, 2014)
Purpose: The aim of this study was to compare the effects of 2 strength and conditioning programs involving either purely vertically oriented or combining vertically and horizontally oriented exercises on soccer-relevant performance variables (ie, acceleration, jumping ability, peak power, and endurance). Methods: Twenty-two professional male soccer players were randomly assigned to 2 training groups: vertical strength (VS, n = 11) and vertical and horizontal strength (VHS, n = 11). Players trained 2 times per week during all the preseason (5 wk) and 3 weeks of the competitive season. The effect of the training protocols was assessed using doubleand single-leg vertical countermovement jumps (CMJ), half-squat peak power (PP), sprint performance over 5 and 15 m, and blood lactate concentration at selected running speeds. Results: Both groups obtained significant improvements in PP (P < .05; ES = 0.87 and 0.80 for VS and VHS, respectively) and small practical improvements in 5-m- (P < .05; ES = 0.27 and 0.25 for VS and VHS, respectively) and 15-m-sprint time (P < .05; ES = 0.19 and 0.24 for VS and VHS, respectively). The CMJ performance showed a small improvement (P < .05, ES = 0.34) only in the VHS group. Submaximal aerobic-fitness changes were similar in both groups (P < .05; ES = 1.89 and 0 .71 for VS and VHS, respectively). Conclusion: This study provided a small amount of practical evidence for the consideration of preseason training protocols that combine exercises for vertical- and horizontal-axis strength development in professional male soccer players. Further studies using more aggressive training protocols involving horizontally oriented conditioning exercises are warranted.